Investigation of congenital syphilis cases: tool for surveillance, permanent education and management - Kamilla Cabral Kosa; Fábia Lisboa de Souza; Marcella Martins Alves Teofilo; Yasmin Nascimento Farias; Márcia Santana; Ana Lúcia Fontes Eppinghaus; Antônio José Leal Costa (DST, 2021)
Introduction: Even though syphilis is an easily detectable and treatable disease, it is still considered a major public health problem, which may lead to Congenital Syphilis (CS). Objective: To analyze the final conclusion and the situations of vulnerability of cases of CS reported in Niterói in 2018 and 2019. Methods: A review of the reported cases of CS, except for abortions, diagnosed in 2018 and 2019, was carried out through SINAN forms and research questionnaires. Results: Of the 46 cases of CS in 2018 and the 107 cases in 2019, 8 (17.4%) and 4 (4%) did not undergo prenatal care, respectively; 2 (4.4%) and 4 (4%) were not screened for CS in the prenatal period; 3 (6.5%) and 13 (12%) were screened, but not treated; 11 (23.9%) and 17 (16%) did not receive an adequate treatment; 1 0 (21.7%) and 23 (21%) were reactive in the screening process, received adequate treatment, but were reinfected; 9 (19.6%) and 32 (30%) were reactive in the screening process, received adequate treatment, but had confirmed CS due to other criteria; 3 (6.5%) and 12 (11%) were nonreactive in prenatal care, but reactive in childbirth; and 0 (0%) and 2 (2%) were reactive, considered a serological scar, untreated, but confirmed by other criteria. The “low-income family” vulnerability aspect appears 21 times in 2018 and 50 times in 2019; “alcohol user”, 11 times in 2018; “frequent change of address”, 18 times in 2019. Conclusion: The social context of pregnant women living in Niterói in 2018 and 2019 may have determined the outcome of congenital syphilis.